Hepatocellular Carcinoma: Consensus, Controversies and Future Directions: A Report from the Canadian Association for the Study of the Liver Hepatocellular Carcinoma Meeting - Kelly Warren Burak; Morris Sherman (Canadian Journal of Gastroenterology and Hepatology)
Hepatocellular carcinoma (HCC) is a leading cause of cancer-related mortality worldwide and its incidence has rapidly increased in North America in recent years. Although there are many published guidelines to assist the clinician, there remain gaps in knowledge and areas of controversy surrounding the diagnosis and management of HCC. In February 2014, the Canadian Association for the Study of the Liver organized a one-day single-topic consensus conference on HCC. Herein, the authors present a summary of the topics covered and the result of voting on consensus statements presented at this meeting.